Telematics in Global Digital Trade: A Case Study of Temu and Shein and Its Implications For E-Commerce Regulations in Indonesia and UNCITRAL - Sutrisno, Andri; Priyono, F.X. Joko; Trihastuti, Nanik (Al-Bayyinah, 2025)
Digital trade has rapidly developed with the support of telematics technology, which enables connectivity among economic actors worldwide. Major e-commerce platforms like Temu and Shein leverage this technology to accelerate product distribution and expand their market reach. Temu, with its business model that directly connects producers and consumers, reduces distribution costs and speeds up delivery. Shein, which adopts a fast fashion model, utilizes telematics-based applications to enhance the speed of production and distribution, as well as to quickly respond to fashion trends. Nevertheless, the global e-commerce sector faces significant regulatory challenges, particularly concerning digital taxation, consumer protection, and personal data protection. In Indonesia, these regulatory challenges become more complex due to cross-border digital transactions involving international platforms that do not fully comply with local regulations. Therefore, this study aims to analyze the role of telematics technology in supporting global digital trade and its impact on e-commerce regulatory policies, as well as to propose policy measures to address the existing challenges. This research uses a qualitative approach with document analysis and literature review from various related sources. The findings indicate that regulatory updates and stronger international cooperation are crucial to addressing cross-border e-commerce regulatory challenges and enhancing consumer protection and fair implementation of digital taxation.